1991
DOI: 10.1530/jrf.0.0910239
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a putative inhibitor of early pregnancy factor in mice

Abstract: Summary. Previous

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Ovaries from 50 superovulated mice were cultured in RPMI-1640 (ICN-Row) with the addition of rat prolactin (PRL-6 ; National Institutes of Health, Bethesda, USA) and medium conditioned by mouse embryos, as described previously (Cavanagh, 1984;Cavanagh et al, 1991b). A control culture was prepared with ovaries from 50 superovulated mice, cultured in RPMI-1640 medium alone; prolactin and mouse embryo-conditioned medium were added at the time of harvest.…”
Section: Mouse Ovary-conditioned Mediummentioning
confidence: 99%
“…Ovaries from 50 superovulated mice were cultured in RPMI-1640 (ICN-Row) with the addition of rat prolactin (PRL-6 ; National Institutes of Health, Bethesda, USA) and medium conditioned by mouse embryos, as described previously (Cavanagh, 1984;Cavanagh et al, 1991b). A control culture was prepared with ovaries from 50 superovulated mice, cultured in RPMI-1640 medium alone; prolactin and mouse embryo-conditioned medium were added at the time of harvest.…”
Section: Mouse Ovary-conditioned Mediummentioning
confidence: 99%
“…We looked for possible protocol differences either in the assay procedures or in the preparation of the samples to explain these differences. Compared with the assay procedure used by Cavanagh et al (1991) we used (i) a different lysis procedure in the preparation of the spleen cells; (ii) human serum as a source of complement not guinea-pig serum and (iii) the cell incubation step was performed in PBS not HBSS. Although these modifications of the assay have been docu¬ mented (Orozco et al, 1986;Clarke et al, 1987) .…”
Section: Introductionmentioning
confidence: 99%
“…Bose et al [10] purified human EPF from the culture medium of preimplantation embryos and reported that EPF had a molecular weight of 14 KD. Smart [5] and other researchers [9][10][11][12] reported that EPF was released from human ova fertilized both in vitro and in vivo, but Morton et al [13], Chen [14], Nahhas et al [15], and Cavanagh et al [16] Bovine (Holstein) ova were obtained by aspirating ovarian follicles (<5 mm) within 4 h of slaughter. After the ova were cultured for 20 h in TCM-199 medium containing 5% fetal calf serum (FCS), they were fertilized in vitro (fertility rate = 50%).…”
mentioning
confidence: 99%